Coordination Strategy for a New Retail Supply Chain Based on Combination Contract - Shuiwang Zhang; Yu Mei; Qiang Bao; Lingzhi Shao (Complexity)
The supply chain in the new retail context demands higher requirements on the price, service, and logistics level. It is very important to seek the coordination among the optimal price, service level, and logistics level. In this paper, we propose the coordination of pricing, the service level, and delivery time of a new retail supply chain composed of one product supplier, one platform service provider, and one logistics provider. Firstly, the profit function mode of product pricing, platform service level, and logistics distribution level that influence the consumers’ demand is constructed in two modes, namely, the centralized and decentralized decision mode. Then, we calculate and compare the optimal product price, the optimal platform service level, the optimal delivery time, and the profit of each member of the supply chain from both decision modes. We discovered that cooperation improves the service level, logistics level, and the income of each member of the new retail supply chain. Therefore, we propose a novel mode called the coordination mode as a strategy for the supply chain based on the combination contract. We performed a numerical analysis to demonstrate the feasibility and effectiveness of the coordination contract.